PENGEMBANGAN KREATIVITAS ANAK MELALUI KEGIATAN MELUKIS DIATAS KANVAS DI PANDEMI - Fivanda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
Obstacles and challenges are still felt related to increasing children's talents and creativity during the pandemic. Children at an early age certainly need learning activities that can stimulate talent and creativity. Early childhood is an age that requires an attitude and learning orientation that can stimulate the potential and basic talents of children. To stimulate this potential, the PKM team took the initiative to hold training on painting on canvas. The PKM team previously conducted PKM activities in providing basic knitting training and amigurumi knitting training. The results of the previous PKM activities had a positive impact and produced products that had entrepreneurial value so that the PKM team continued their collaboration with the Rumah Pagi Bahagia Foundation partners in Bintaro by providing hand painting on canvas training as a way to develop children's creativity during a pandemic. The target participants are foster children aged 8-10 years. The aim of this PKM activity is to have foster children who receive education to support talent and creativity. The activity method is carried out offline. The PKM team has prepared presentation material and video tutorials. Beginning with giving an introduction to the tools and types of canvas to be painted and giving examples of motifs or patterns before painting on a canvas bag. The canvas bag provided is a drawstring bag. Children can be creative with imagination and desire for pictures to be hand painted. Mandatory outputs from this activity will be presented and published in a scientific meeting seminar. Additional output copyright video tutorial from the PKM team. This training is expected to be a solution in increasing the talent and creativity of early childhood whose activities are of course limited during the pandemic. Hambatan dan tantangan masih dirasakan berkaitan dengan peningkatan bakat serta kreativitas anak pada masa pandemi. Anak dengan usia dini tentunya memerlukan kegiatan pembelajaran yang mampu menstimulus bakat dan kreativitas. Anak usia dini merupakan usia yang membutuhkan orientasi sikap dan belajar yang dapat merangsang potensi dan bakat dasar anak. Untuk menstimulus potensi tersebut maka, tim PKM berinisiatif untuk mengadakan pelatihan melukis diatas kanvas. Tim PKM sebelumnya telah melakukan kegiatan PKM dalam memberikan pelatihan dasar merajut dan pelatihan merajut amigurumi. Hasil dari kegiatan PKM sebelumnya memberikan dampak positif dan menghasilkan produk yang memiliki nilai kewirausahaan sehingga tim PKM melanjutkan kerjasama dengan mitra Yayasan Rumah Pagi Bahagia di Bintaro dengan memberikan pelatihan melukis diatas kanvas sebagai pengembangan kreativitas anak di masa pandemi. Target peserta dari anak asuh berusia 8-10 tahun. Tujuan dari kegiatan PKM ini memiliki anak asuh yang mendapatkan pendidikan penunjang bakat dan kreativitas. Metode kegiatan dilaksanakan secara luring. Tim PKM sudah mempersiapkan materi presentasi dan video tutorial. Diawali dengan memberikan pengenalan alat dan jenis kanvas yang akan dilukis serta memberikan contoh motif atau pola sebelum melukis pada tas kanvas. Tas kanvas yang dipersiapkan yaitu tas serut. Anak-anak dapat berkreasi dengan imajinasi dan keinginan untuk gambar yang akan di hand painting. Luaran wajib dari kegiatan ini akan dipresentasikan dan dipublikasi dalam seminar temu ilmiah. Luaran tambahan hak cipta video tutorial dari tim PKM. Pelatihan ini diharapkan dapat menjadi solusi dalam meningkatkan bakat dan kreativitas anak usia dini yang tentunya terbatas kegiatannya selama pandemi.